Metal complexes of curcumin – synthetic strategies, structures and medicinal applications. (12th May 2015) - Wanninger, Simon; Lorenz, Volker; Subhan, Abdus; Edelmann, Frank T.
Abstract : This Tutorial Review provides the first general overview on synthesis and medicinal applications of metal curcumin complexes, including anticancer activity and anti-Alzheimer's disease activity. Abstract : This Tutorial Review presents an overview on the synthesis, characterization and applications of metal complexes containing curcumin (=1, 7-bis(4-hydroxy-3-methoxyphenyl)-1, 6-heptadiene-3, 5-dione) and its derivatives as ligands. Innovative synthetic strategies leading to soluble and crystallizable metal curcumin complexes are outlined in detail. Special emphasis is placed on the highly promising and exciting medicinal applications of metal curcumin complexes, with the three most important areas being anticancer activity and selective cytotoxicity, anti-Alzheimer's disease activity, and antioxidative/neuroprotective effects. Overall, this Tutorial Review provides the first general overview of this emerging and rapidly expanding field of interdisciplinary research.